In the perception of the Olympic movement and gender equity in sport, are gender and sport practice determining factors? - Muñoz-Helú, Hussein; Reynoso-Sánchez, Luis Felipe; Cruz-Morales, Karla Noelia; Salazar-C, Ciria Margarita; Mataruna-Dos-Santos, Leonardo Jose (Frontiers in Sports and Active Living, 2025)
BackgroundThe Olympic Movement (OM) has evolved considerably, with the modern Olympic Games as its main emblem in the world. Within its most recent agenda, issues such as sustainability, fair play, however, inclusion and gender equity have gained greater relevance, especially through Olympic Agenda 2020, its subsequent recommendations in Agenda 2020 + 5 and the strong influence of the Sustainable Development Goals (SDGs) promoted by the United Nations (UN). This study analyzes the conditional role of gender and sports practice level in moderating the influence of the Olympic Movement's perception on attitudes toward women's participation in sports among Mexican university physical education, sports, and exercise sciences students.MethodA cross-sectional, correlational-descriptive design was employed with a sample of 415 students (33.5% women) from 15 higher Mexican education institutions. Data collection utilized the Olympism Vision and Its Educational Repercussions Questionnaire and the Scale of Attitudes Toward Women's Participation in Sports. A double moderation analysis examined how gender and sports practice level moderated the relationship between Olympic Movement perceptions (threats, values, significance) and attitudes toward women's sports participation.ResultsWomen exhibit greater knowledge of Olympism than men, as do high-level sports practitioners compared to their less active counterparts. Women also express a stronger positive perception of women in sports but report lower perceptions of equity and social support for women in sports compared to men. Double moderation analyses revealed that gender and sports practice level significantly shaped the relationship between perceptions of the Olympic Movement and attitudes toward women's sports participation. Women at low-to-moderate sports participation levels perceived greater threats to gender equity and more strongly identified with the Olympic Movement's values in promoting women's participation. Elite athletes of both genders recognized gender inequities within sports systems, while non-active participants linked women's participation to Olympic ideals over systemic actions.ConclusionThe results underscore the need for targeted policies and educational strategies to enhance gender equity and support women's sports participation. Promoting Olympic education within academic and extracurricular frameworks could strengthen critical awareness of human rights and sports values, countering stereotyped narratives and fostering equitable opportunities in sports.